2021
DOI: 10.5539/ijbm.v16n9p82
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Mobile Payment Adoption: Customers’ Trends and Challenges

Abstract: The continuous advancement of the mobile technology industry and the wide acceptance of mobile devices worldwide have provided great prospects to customers regarding their monetary transactions. As a result, numerous individuals use their mobile devices, mainly their smartphone; to pay online and even more are expected to take advantage of the mobile payments in the near future. This study conducts an up-to-date review to survey the landscape of individuals’ behavioral intention to adopt m-payments s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…A study conducted by Schierz et al (2010) suggests that users are likely to continue using the traditional payment mechanisms if they feel a higher level of risk in adopting the newer payment systems. Some of the researchers have also indicated that PR acts as a crucial determinant, particularly during the pre-adoption phase, where consumers do not have the relevant technical/functional experience of using a novel technology and consider using a new technology risky (Saprikis and Vlachopoulou, 2021). Thus, the following hypothesis has been proposed:…”
Section: Intention To Adopt Mobile Payment Systemsmentioning
confidence: 99%
“…A study conducted by Schierz et al (2010) suggests that users are likely to continue using the traditional payment mechanisms if they feel a higher level of risk in adopting the newer payment systems. Some of the researchers have also indicated that PR acts as a crucial determinant, particularly during the pre-adoption phase, where consumers do not have the relevant technical/functional experience of using a novel technology and consider using a new technology risky (Saprikis and Vlachopoulou, 2021). Thus, the following hypothesis has been proposed:…”
Section: Intention To Adopt Mobile Payment Systemsmentioning
confidence: 99%
“…In the context of this evolving landscape, understanding the research problem becomes paramount. While mobile payment technology has witnessed significant growth and adoption [1], [6], [8], [11], [12], there exist gaps and challenges that warrant exploration. These may include issues related to security, interoperability, user experience, and regulatory compliance.…”
Section: Introductionmentioning
confidence: 99%